Reverse logistics in a system of the circular economy: theoretical aspect - Zaloznova, Yu.; Kwilinski, A.; Trushkina, N. (Економічний вісник Донбасу, 2018)
The evolutionary development and stages of formation of the concept of «green» logistics have been studies. Based on the analysis and generalization of the existing scientific approaches to the definition of the term «green logistics» they are systematized into 7 classification groups: such as scientific line; economic activity; factor of preservation of the environment through environmentally friendly technology; environmental safety tool in the context of the integrated system; set of logistic approaches to optimization of waste flows and resources; transport distribution system; attempt to develop an environmentally compatible product. It is established that the majority of scientists identify the concept of «green» and «environmental logistics», which means a set of actions aimed at minimization of the environmental impact of logistics activities; integrated management of logistics processes (production, storage, transportation of waste); subsystem of control of flow of products with a minimum level of eco-destructive impact of economic activity on the environment; from the point of view of a systematic approach as a scientific line, which involves the use of modern innovative logistics technologies.
Scientific approaches to the definition of «reverse logistics» are classified into 8 groups: modern concept of waste management; waste flow management system; process of planning, realization and control of logistic goods flows from the sphere of turnover and consumption as a result of the reverse distribution of finished products; moving products from the point of its consumption to the point of its production in order to restore its value or provide its recycling; return of material after user to manufacturer through recycled cooperatives; logistic approaches to optimize the waste flow stream; logistics of returned goods or reverse material flows; the process of returning inventory items from the consumer to manufacturer.
Proprietary formulation of the concept of «reverse logistics» as a type of economic activity is given the processes of storage, transportation, environmentally safe storage, recycling (recycling and disposal) of waste, which can reduce the negative impact on ecosystems and the environment.
The implementation of reverse logistics tools will minimize the cost of the process of waste flow while maintaining the necessary level of environmental safety, which is one of the important requirements for the implementation of integrated waste management systems under modern conditions of the development of the circular economy. Досліджено еволюційний розвиток і етапи становлення концепції «зеленої» логістики. На основі аналізу й узагальнення існуючих наукових підходів до визначення терміна «зелена логістика» їх систематизовано за 7 класифікаційними групами: як науковий напрям; господарська діяльність; чинник збереження дов¬кілля за допомогою екологічно чистих технологій; інструмент забезпечення екологічної безпеки цілісної системи; сукупність логістичних підходів до оптимізації потоків відходів і ресурсів; транспортна система розподілу; спроба розробки екологічно сумісного продукту. Встановлено, що більшість науковців ототожнюють поняття «зелена» та «екологічна логістика», під якою розуміється науковий напрям, що передбачає використання сучасних інноваційний логістичних технологій; сукупність дій, спрямованих на мінімізацію екологічних наслідків логістичної діяльності; інтегроване управління логістичними процесами (виробництво, складування, транспортування відходів); підсистема управління потоками продукції від постачальника до споживача з мінімальним впливом на довкілля. Наукові підходи до визначення поняття «реверсивна логістика» класифіковано за 8 групами: сучасна концепція управління відходами; система управління рухом відходів; логістичні підходи до оптимізації руху відходів; логістика повернутих товарів або зворотних матеріальних потоків; процес повернення товарно-матеріальних цінностей від споживача до виробника; процес планування, реалізації й контролю логістичних товаропотоків зі сфери обігу й споживання в результаті зворотного розподілу готової продукції; переміщення продукції з точки її споживання в точку її виробництва з метою відновлення її цінності або забезпечення її утилізації; повернення матеріалу після споживача до виробника через рециркулярні кооперативи. Надано авторське формулювання поняття «реверсивна логістика» як виду господарської діяльності, яка включає процеси складу-
вання, транспортування, екологічно безпечного зберігання, рециклінгу (вторинної переробки й утилізації) відходів, що дозволяє зменшити негативний вплив на екосистеми та довкілля. Реалізація інструментів реверсивної логістики сприяє мінімізації витрат на процес проходження потоків відходів з одночасною підтримкою необхідного рівня екологічної безпеки, що є однією із важливих вимог до впровадження інтегрованих систем управління відходами в сучасних умовах розвитку циркулярної економіки. Исследованы эволюционное развитие и этапы становления концепции «зеленой» логистики. На основе анализа и обобщения существующих научных подходов к определению термина «зеленая логистика» их систематизировано по 7 классификационным группам: как научное направление; хозяйственная деятельность; фактор сохранения окружающей среды с помощью экологически чистых технологий; инструмент обеспечения экологической безопасности целостной системы; совокупность логистических подходов к оптимизации потоков отходов и ресурсов; транспортная система распределения; попытка разработки экологически совместимого продукта. Установлено, что большинство исследователей отождествляют понятия «зеленая» и «экологическая логистика», под которой понимается научное направление, предусматривающее использование современных инновационных логистических технологий; совокупность действий, направленных на минимизацию экологических последствий логистической деятельности; интегрированное управление логистическими процессами (производство, складирование, транспортировка отходов); подсистема управления потоками продукции от поставщика к потребителю с минимальным влиянием на окружающую природную среду. Научные подходы к определению понятия «реверсивная логистика» классифицированы по 8 группам: современная концепция управления отходами; система управления движением отходов; логистические подходы к оптимизации движения отходов; логистика возвращенных товаров или обратных материальных потоков; процесс возврата товарно-материальных ценностей от потребителя к производителю; процесс планирования, реализации и контроля логистических товаропотоков из сферы обращения и потребления в результате обратного распределения готовой продукции; перемещение продукции с точки ее потребления в точку ее производства с целью возврата ценности или обеспечения ее утилизации; возвращение материала после потребителя к производителю через рециркулирующие кооперативы. Дано авторское формулирование понятия «реверсивная логистика» как вида хозяйственной деятельности, которая включает процессы складирования, транспортировки, экологически безопасного хранения, рециклинга (вторичной переработки и утилизации) отходов, что позволяет уменьшить негативное влияние на экосистемы и окружающую природную среду. Реализация инструментов реверсивной логистики способствует минимизации затрат на процесс прохождения потоков отходов с одновременной поддержкой необходимого уровня экологической безопасности, что является одним из важнейших требований к внедрению интегрированных систем управления отходами в современных условиях развития циркулярной экономики.